In the eye of the beholder: investigating authority legitimization from distinct theoretical perspectives - Iwanowska, Bożena; Majczyk, Julita; Kapranov, Yan (Journal of Modern Science, 2025)
Objectives This research critically examines legitimization in illiberal democracies, emphasizing its influence on governance. Material and methods This research explores legitimization across political, business, and socio-cultural spheres, using a focused analysis to compare normative and positivist perspectives, specifically David Beetham's and Jean d'Aspremont's. It examines authority legitimization, analyzing its connections with authority, government, law, and democracy, focusing on legitimacy of origin and exercise. Results Beetham argues that power and legitimacy are closely intertwined. Legitimacy includes compliance, rationalization based on popular beliefs and explicit consent. D'Aspremont's work on government legitimization, emphasizing the importance of origins and practices, is linked with democratic principles. It suggests that origin legitimacy evaluates the source of authority, typically linked to democratic elections, while action legitimacy examines the exercise of authority. Conclusions Beetham and d'Aspremont's analyses of authority legitimization and legitimacy's roots highlight the significance of understanding power's legitimization for sociology, political theory, and philosophy. Their work reveals its importance for scientists, politicians, and business leaders alike. For scientists, it informs ethical research and policy development. Politicians gain insights for crafting policies that resonate with the public, enhancing governance. Business leaders, through these principles, can improve corporate governance and build stakeholder trust. Understanding normative and positivist approaches to legitimacy can guide leaders to make decisions that are effective, ethical, and widely accepted, emphasizing legitimacy's role in enhancing practices across various fields.